Leprosy and its prejudice today (Research, Society and Development, 2023)
Leprosy is considered a major public health problem, and in developing countries. In this way, the objective of this article was to carry out a documental research to identify the reasons for the resistance of patients to the treatment of leprosy. The present study is an integrative literature review. The synthesis of the results was carried out through the integration of the data obtained from the selected studies and presented in a clear and objective way. Leprosy, also known as leprosy, is a pathology that has Egyptian reports since 4266 BC. Leprosy is caused by the bacillus Mycobacterium leprae, or Hansen's bacillus. This consists of an obligate intracellular parasite, with affinity for skin cells and peripheral nerve cells, which, after being installed in the body of an infected individual, spreads. The mode of transmission of Leprosy is still a controversial topic, but it is believed that transmission occurs through prolonged and close contact with infected people. It is essential that health professionals are trained to deal with the disease in a humane way, and that the population is informed about the signs and symptoms of the disease, as well as the preventive and treatment measures available.